Effects Of Antioxidant Vitamins On The Expression Of Nrf2/Keap1 Signaling Molecules In Liver Against PCB Induced Experimental Diabetic Rats (Journal of Namibian Studies : History Politics Culture, 2023)
Background: Polychlorinated biphenyl, or PCB, consists of biphenyl rings with a fluctuating number of chlorine compounds attached to it; approximately 209 such compounds have been found to date. Antioxidant vitamins are really important for the body. Vitamins C and E are two of them. While vitamin C acts as a water-soluble antioxidant and vitamin E acts as a major chain-breaking antioxidant, they have been continuously exploited for their beneficial effects against oxidative stress. Oxidative stress is the imbalance between the production and accumulation of oxygen-reactive species, which play several pathological roles in cell signaling. Aim: The study was designed to assess the effects of antioxidant vitamins on the expression of Nrf2/Keap1 signaling molecules in PCB induced experimental rats.Methods: Adult male Wistar rats weighing 180–200 g were used for this study. The experimental groups were divided into three groups (control, test group, and treatment group). Total RNA isolation was followed by reverse transcriptase-aided RNA to cDNA conversion and mRNA expression, which were analyzed by RT-PCR. The statistical analysis was performed using one-way analysis of variance (ANOVA), followed by Duncan's multiple range test to determine statistical significance among the groups.Results: The findings of this study confirmed that exposure to PCB can alter the FBG level and serum insulin levels. Furthermore, mRNA expression results proved that expression of Nrf2 was significantly (p